Security in wireless LANs and MANs - Hardjono, Thomas (Artech House computer security series., 2005)
With the popularity of the Wireless Local Area Network (WLAN) standard 802.11 WiFi and the growing interest in the next generation Wireless Metropolitan Area Network (WMAN) standard 802.16 WiMax, the need for effective solutions to the inherent security weaknesses of these networking technologies has become of critical importance. Thoroughly explaining the risks associated with deploying WLAN and WMAN networks, this groundbreaking book offers you practical insight into identifying and overcoming these security issues.nnIncluding detailed descriptions of possible solutions to a number of specific security problems, the book gives you the hands-on techniques that you need to secure wireless networks in the enterprise and the home. This handy reference also defines key security terms to help you fully understand concepts and evaluate security products on the market today. Moreover, the book discusses the future direction of the WLAN and WMAN industry, allowing you to plan ahead for emerging technologies in the field.